Legal Implications of Mixed Marriages on the Status of Children's Inheritance in Indonesia - sharla shela; Nurita lingsu; mariana oktaviani (Yayasan Cinta Negara, 2025)
Mixed marriages between Indonesian citizens and foreign nationals are increasing in line with globalization. However, this condition raises legal challenges, especially regarding the inheritance status of children born from these marriages. This study aims to analyze the legal implications of mixed marriages on children's inheritance rights in Indonesia based on the applicable legal system, namely the Civil Code, Islamic law, and customary law. The method used is a normative juridical approach by analyzing legislation, court decisions, and relevant legal literature. The results show that the child's citizenship status, the legality of the parents' marriage, and the legal system used have a significant effect on the child's inheritance rights. Disharmony between various legal systems in Indonesia often leads to legal uncertainty in the settlement of disputes over the inheritance of children from mixed marriages. Therefore, it is necessary to harmonize regulations and increase legal protection of children's rights in the context of inheritance